Transmission of COVID-19 in the presence of single-dose and double-dose vaccines with hesitancy: mathematical modeling and optimal control analysis - Wangari, Isaac Mwangi; Olaniyi, Samson; Lebelo, Ramoshweu S.; Okosun, Kazeem O. (Frontiers in Applied Mathematics and Statistics, 2023)
This paper tracks the transmission dynamics of SARS-CoV-2 virus (severe acute respiratory syndrome corona virus 2) using a non-linear deterministic system. The proposed model accounts for the unwillingness of both susceptible and partially vaccinated individuals to receive either single dose or double dose vaccine (vaccine hesitancy). Results by center manifold theory which are supported by numerical results show that, if the COVID-19 vaccines administered are imperfect and transient then there exist a parameter space where backward bifurcation occurs.Time profile projections depict that in a setting where vaccine hesitancy is present, administering single dose vaccines leads to a significant reduction of COVID-19 prevalence than when double dose vaccines are administered. Comparison of the impact of vaccine hesitancy against either single dose or double dose on COVID-19 prevalence reveals that vaccine hesitancy against single dose is more detrimental than vaccine hesitancy against a double dose vaccine. The model is extended to incorporate three time-dependent non-pharmaceutical and pharmaceutical intervention controls, namely preventive control, control associated with screening-management of both truly asymptomatic and symptomatic infectious individuals and control associated with vaccination of susceptible individuals with a single dose vaccine. The Pontryagin's Maximum Principle was applied to establish the optimality conditions associated with the optimal controls. Using fourth-order Runge-Kutta forward backward sweep numerical scheme, it is revealed that non-pharmaceutical time-dependent control significantly flattens the COVID-19 epidemic curve 1 Wangari et al.when compared with pharmaceutical controls. Cost-effectiveness assessment suggest that nonpharmaceutical control is the most cost-effective COVID-19 mitigation strategy that should be implemented in a setting where resources are limited.